The relationship between the distance of hospitals on highways and the increased suffering of paramedics in emergency situations - Mamdouh Turki Eidhah Altharmani,; Mansour Farhan Thuwayb Algethami,; Yousef Saad Awadh Alnefaie,; Mesfer Dhawi Khatim Algethami,; Faraj Dhafer F Alshehri,; Yunus Ibrahim H Alzubaidi,; Fahad Ali Saad Algarni, (International Journal of Medical Toxicology and Legal Medicine, 2024)
The current study aimed to identify the relationship between the distance of hospitals from highways and the increased suffering of paramedics in emergency cases. The study relied on the descriptive analytical approach and relied on a sample of 200 paramedics and distributed the electronic questionnaire form to the sample electronically. The study concluded with a set of results, the most important and prominent of which is that there is a statistically significant relationship between the distance of hospitals from highways and the increased suffering of paramedics in emergency cases. Delays in reaching the hospital reduce the efficiency of medical intervention in emergenciesn. The current distribution of hospitals is disproportionate to the density of accidents on highways.The presence of nearby field hospitals can alleviate the suffering of paramedics and patients. Poor infrastructure around highways increases obstacles to emergency response. Implementing advanced systems for hospital distribution addresses current emergency issues.